An Improved Genetic Algorithm and Its Application - Xuesong Yan; Qinghua Wu; Can Zhang; Wei Li; Wei Chen; Wenjing Luo (Institute of Advanced Engineering and Science, 2012)
Traditional genetic algorithm trapped into the local minimum easily. Therefore, based on a simple genetic algorithm and combine the base ideology of orthogonal design method then applied it to the population initialization, using the intergenerational elite mechanism, as well as the introduction of adaptive local search operator to prevent trapped into the local minimum and improve the convergence speed to form a new genetic algorithm. Through the series of numerical experiments, the new algorithm has been proved to be efficiency. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1265